PENGARUH TEKNIK BRAIN GYM TERHADAP PENINGKATAN KONSENTRASI BELAJAR SISWA SMP BPPI BALEENDAH BANDUNG DALAM PROSES PEMBELAJARAN DI KELAS - Ika Rasanty; Janice Heliya Permatasari; Widia Yunita; Nani Suharyani; Rifqi Farisan Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning concentration is an important internal factor for successful learning, yet some seventh-grade students at SMP BPPI Baleendah Bandung reportedly struggle to maintain focus during lessons, particularly due to noisy classroom conditions, fatigue, and accumulated cognitive load during afternoon periods. This study aimed to examine the effect of the brain gym technique on improving students learning concentration. The study used a true experimental design with a Pretest-Posttest Control Group Design, involving 20 seventh-grade students randomly assigned to an experimental group (n=9) who received approximately ten minutes of brain gym treatment, and a control group (n=11) who received no treatment. Data were collected using a learning concentration scale and analyzed using the Shapiro-Wilk test for normality and the Mann-Whitney U test for between-group differences. Results showed the experimental group's mean score was slightly higher than the control group's, but the hypothesis test yielded a significance value of 0.790, indicating no statistically meaningful difference. Thus, based on the data analyzed, brain gym did not show a significant effect on improving students learning concentration, which may be related to the limited number of subjects and the single treatment session provided.